Deflection Behavior of Reinforced Concrete Beam Frame System with 3/4 Spacing Effective Height of The Beam - Huwae, David D. M.; Frans, Pieter L.; Parera, Lydia R. (International Journal of Multidisciplinary: Applied Business and Education Research, 2024)
This study aimed to analyze the deflection behavior of reinforced concrete beams with a spacing of 3/4 of the effective beam height. This research is a laboratory experimental study with a design of 6 (six) test objects consisting of 3 (three) normal beams (BN) as control variable beams and 3 (three) reinforcing beams of the frame system with a spacing of 0.75d (BTR75 ) as the independent variable. Data were analyzed using the strength design method. The results showed that the deflection behavior of reinforced concrete beams with a spacing of 3/4 of the effective beam height (BTR75) had better serviceability and increased the flexural capacity of Mu beams up to 4.60% and reduced the amount of deflection of the beam BN.